Avaliação da espessura do esmalte proximal em segundos pré-molares superiores humanos e sua correlação com o diâmetro mésio-distal - Fischer, Luís Henrique (2006)
The thickness determination of adjacent enamel at the height of the contact point is very important, seem that the erosion of this dental part is often used in orthodontic clinic to know the dental divergence and treatment stability correction. With the intention to determinate the mésio-distal diameter values and give the thickness average values of enamel in the adjacent sides at the contact’s point height, were rated 42 second superior pre-molar teeth, 20 lefts and 22 rights. The mésio-distal diameter, were measured with digital pachymeter help and then, were included in resin and cut, having a central foil of 0,7 mm (thickness), allowing the tickness enamel measure in millesimal precision outline machine. Considering that were also analysed the relationship possibilities between the enamel thickness at the proximal face and mésio-distal diameter. The results show that the medium value of the mesio-distal diameter is 6,85 mm to the second superior pre-molar tooth and with the average’s thickness of enamel 1,101 mm at mesial and 1,157 mm at distal. According with Spearman and Pearson’s testes were found significant statistically correlation at the right side between the enamel thickness mesial face and mesio distal diameter, between the tickness at distal face and mesio distal diameter. At the left side were found positive correlations between the distal enamel thickness and mesio distal diameter. In both sides, there were significant statistically correlation between the distal enamel thickness and mesio distal diameter. In both sides, there were significant statistically correlation between the mesial enamel thickness and distal enamel thickness. Independent of the side, the enamel thickness average is bigger at distal face than mesial